The importance of organic amendments in soil conservation and agricultural production - Murillo Montoya, Sergio Adrián; Mendoza Mora, Alexander; Fadul Vásquez, Carlos Julio (Revista Colombiana de Investigaciones Agroindustriales, 2020)
Organic amendments are used to improve the soil physical, chemical and microbiological conditions, allowing to increase the availability ofe macro and micronutrients necessary for plants to improve their production. Among the main organic amendments are green manures, sewage sludge, manure and vermicompost, which combined with efficient microorganisms, have the potential to improve water availability for plants, reduce greenhouse gas emissions, and recover degraded soils, reduce erosion, sequester heavy metals and carbon, and solubilize macro and micronutrients necessary for plants. As a consequence of the above, this review explored the different types of organic amendments that are used worldwide, evaluated the impact of the addition of efficient microorganisms in organic amendments and determined the impact of organic amendments on agricultural production. It was found that, worldwide, amendments are used as cheaper and more affordable alternatives than synthetic fertilizers.